Innovation Strategy the Development of Competitifeness of Eco-Based Coastal Tourism Destination, Management Organization and Quality of Services - UDIYANA, Ida Bagus Gede; SUASTAMA, Ida Bagus Radendra; ASTINI, Ni Nyoman Seri; MAHANAVAMI, Gusti Ayu; KARWINI, Ni Ketut; MARETTA, Yoris Adi (Journal of Environmental Management and Tourism; Vol 9 No 4 (2018): JEMT Volume IX Issue 4(28) Summer 2018, 2018)
This study aims to identify the condition of internal factors, external factors and the formulation of innovation strategies for the development of competitiveness of eco-based coastal tourism destinations, management organizations and service quality. This type of research is qualitative research. Methods of data collection using methods of observation, documentation and interviews. Respondents are determined purposively based on the purpose of this research. Data analysis techniques used are Internal Factor Analysis Strategic (IFAS), External Factor Analysis Strategic (EFAS) and SWOT matrix model. The results of this study indicate that the internal factor condition consists of strengths showing that natural conditions white sandy beaches, calm blue water and strong community support. Desa Pakraman organization and management are given full authority and responsibility to manage this coastal tourist destination. The weakness is the low entrepreneurial spirit and the quality of local human resources, as well as the preservation of the environment. External factors indicate that opportunities are based on the economic aspect of improving entrepreneurship and empowering local entrepreneurs to own and manage businesses, and strong synergy among stakeholders. Threats to coastal tourism destinations are land tenure by investors, regional carrying capacity, exploitation and environmental pollution. The main strategies for developing coastal tourism destinations through Growth Inovation Strategy are formulated through innovation and infrastructure innovation strategies, organizational innovation and management strategies and innovative service quality strategies.